Novel Partitivirus Enhances Virulence of and Causes Aberrant Gene Expression in Talaromyces marneffei - Susanna K. P. Lau (American Society for Microbiology, 2018)
ABSTRACT Talaromyces marneffei is the most important thermal dimorphic fungus causing systemic mycosis in Southeast Asia. We report the discovery of a novel partitivirus, Talaromyces marneffei partitivirus-1 (TmPV1). TmPV1 was detected in 7 (12.7%) of 55 clinical T. marneffei isolates. Complete genome sequencing of the seven TmPV1 isolates revealed two double-stranded RNA (dsRNA) segments encoding RNA-dependent RNA polymerase (RdRp) and capsid protein, respectively. Phylogenetic analysis showed that TmPV1 occupied a distinct clade among the members of the genus Gammapartitivirus. Transmission electron microscopy confirmed the presence of isometric, nonenveloped viral particles of 30 to 45 nm in diameter, compatible with partitiviruses, in TmPV1-infected T. marneffei. Quantitative reverse transcription-PCR (qRT-PCR) demonstrated higher viral load of TmPV1 in the yeast phase than in the mycelial phase of T. marneffei. Two virus-free isolates, PM1 and PM41, were successfully infected by purified TmPV1 using protoplast transfection. Mice challenged with TmPV1-infected T. marneffei isolates showed significantly shortened survival time (P < 0.0001) and higher fungal burden in organs than mice challenged with isogenic TmPV1-free isolates. Transcriptomic analysis showed that TmPV1 causes aberrant expression of various genes in T. marneffei, with upregulation of potential virulence factors and suppression of RNA interference (RNAi)-related genes. This is the first report of a mycovirus in a thermally dimorphic fungus. Further studies are required to ascertain the mechanism whereby TmPV1 enhances the virulence of T. marneffei in mice and the potential role of RNAi-related genes in antiviral defense in T. marneffei. IMPORTANCE Talaromyces marneffei (formerly Penicillium marneffei) is the most important thermal dimorphic fungus in Southeast Asia, causing highly fatal systemic penicilliosis in HIV-infected and immunocompromised patients. We discovered a novel mycovirus, TmPV1, in seven clinical isolates of T. marneffei. TmPV1 belongs to the genus Gammapartitivirus of the family Partitiviridae. We showed that TmPV1 enhanced the virulence of T. marneffei in mice, with shortened survival time and higher fungal burden in the organs of mice challenged with TmPV1-infected T. marneffei isolates than in those of mice challenged with virus-free isogenic isolates. Transcriptomics analysis showed that TmPV1 altered the expression of genes involved in various cellular processes in T. marneffei, with upregulation of potential virulence factors and suppression of RNAi machinery which may be involved in antiviral defense. This is the first report of a mycovirus in a thermal dimorphic fungus. The present results offer insights into mycovirus-fungus interactions and pathogenesis of thermal dimorphic fungi.